2022
DOI: 10.3390/economies10100258
|View full text |Cite
|
Sign up to set email alerts
|

The Global Textile and Apparel Value Chain: From Mexico–US–China Linkages to a Global Approach

Abstract: The aim of this paper is to analyze the participation in the global textile and apparel value chain with special attention, first, to the case of three dynamic and interrelated economies (Mexico, the United States, and China); and second, to a general approach to a larger sample of countries through the analysis of trade in value added. From the descriptive analysis, a high domestic share in each country’s exports is found. However, China is the leading exporter in the industry, accounting for around a third o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…China is the world's biggest producer of apparel. China's exports of apparel were $291 billion in 2020 or around 35% of the global market (Rodil-Marzábal et al, 2022). But as per a study done on barriers which challenge in embedding environmental sustainability practices in Chinese apparel sector has found that lack of environmental missions in the organizational culture is a key barrier when implementing environmental sustainability practices in the apparel sector (Zhu et al, 2005).…”
Section: Poor Organizational Culturementioning
confidence: 99%
“…China is the world's biggest producer of apparel. China's exports of apparel were $291 billion in 2020 or around 35% of the global market (Rodil-Marzábal et al, 2022). But as per a study done on barriers which challenge in embedding environmental sustainability practices in Chinese apparel sector has found that lack of environmental missions in the organizational culture is a key barrier when implementing environmental sustainability practices in the apparel sector (Zhu et al, 2005).…”
Section: Poor Organizational Culturementioning
confidence: 99%
“…This is developed by the process designer according to the product requirements. (3) The state data layer: It refers to the relevant data collected and stored in a time-series database at different collection intervals using devices such as sensors, monitoring equipment, and automatic collection instruments.…”
Section: Knowledge Modeling and Graph Generation In Textile And Appar...mentioning
confidence: 99%
“…Textile and apparel production is an important economic pillar in China [1][2][3]. Currently, the traditional apparel production mode is rapidly shifting to customized garment production, increasing the demand for the intelligent customization of orders [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a well‐developed supply chain structure and prosperous demand, China is the most important sourcing base and the biggest market in the global fashion industry. China is recognized as the most dynamic clothing exporter in the world since it joined the World Trade Organization in 2001 with great contributions to the global textile and apparel value chain (Rodil‐Marzábal, 2022). China ranks top in the global textile and clothing export business, with a total export cumulative value of US$315.5 billion, accounting for 43.5% and 31.6% of the global textile and clothing exportation, respectively (FashionUnited, 2022; Kastner, 2022).…”
Section: Introductionmentioning
confidence: 99%